Gambaran Pola Asuh Orangtua yang Menikah Dini dalam Menanamkan Kedisiplinan pada Anak - Sobur Setiawan; Tetti Solehati; Udin Rosidin (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Early marriage is a marriage conducted at the age ofe adolescents. Women who are early married are at risk of reproductive health and psychologis and marriage rates in Indonesia were still high so it is feared are at risk of reproductive healt and psychologis increase too. Early marriage can be influenced by several factors, one of which is parenting. The purpose of this research was to description the role of early married parents to investing discipline. The research method used quantitative descriptive with cross sectional approach. The sampling technique used total sampling with a total of 32 respondents. The instruments compiled by researchers with validity and reliability tests results of 0.392-0.863 with r tables of 0.361 with Alpha Cronbach 0.913. The analyzed used a frequuency and percentage distribution. The study was conducted at Rancabango village, Tarogong Kaler Sub-district in the District of Garut in September 2019 after being approved by Padjadjaran University Research Ethics Committee with the letter No.1130/UN6.KEP/EC/2019. The results of this research showed that the role of early married parents in the category of democratic (59.4%), authoritarian (40.6%), permissive (37.5%). Based on the data it can be concluded that parenting of parents who married early in instilling discipline to children was democratic parenting, however authoritarian and permissive types are also high therefore early marriage must be avoided by maintaining parenting to children.